The environmental impact assessment (EIA) under the Lesotho Environment Act No. 10 of 2008 : a comparative analysis with the South African EIA regime. - Tapole, Amandus Thabang. (2013)
Environmental Impact Assessment (EIA) has become common as the world realise that the environment has to be managed well for sustenance of life on the planet. As the EIA has now become a sine qua non in the management of the environment, the issue is how to ensure that it is best employed to achieve the desired results. There are various approaches that countries have used in their EIA processes, but it appears that the most efficient application emanates from having a legal basis for its use. The two countries which are subjects of this study, Lesotho and South Africa, have been chosen primarily because of their geographic proximity to each other, which factor often exposes them to similar environmental experiences. Their response to such environmental challenges then becomes important. This study concentrates on statutory enactments in terms of the EIA processes by the two countries. Their EIA regimes are compared and contrasted. This is done against the background of what is considered the best international EIA practice. It is revealed that the two countries are not at par in their use of and experience with the EIA process. While Lesotho is encouraged to enrich its new practise from South African experiences with the EIA, South Africa too has some way to go towards the best EIA practice. === Thesis (LL.M.)-University of KwaZulu-Natal, Pietermaritzburg, 2011.